UTILIZING BEHAVIOR MANAGEMENT STRATEGIES TO ENHANCE ENGAGEMENT AND DISCIPLINE IN ENGLISH LEARNING CLASSROOM WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) STUDENTS AT SLB NEGERI 1 MAKASSAR - Nur Intan; Eka Prabawati Rum; Hilda Hafid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the implementation of behavioral management strategies used by English teachers to improve engagement and discipline among students with attention deficit hyperactivity disorder (ADHD) at SLB Negeri 1 Makassar. This study uses a qualitative descriptive approach through non-participatory classroom observation and field notes. The strategies observed included positive reinforcement, clear and structured instructions, and the use of visual aids. The findings show that these strategies effectively improve students' cognitive, emotional, and behavioral engagement, as well as aspects of discipline such as compliance with rules, impulse control, and reduction of disruptive behavior. Positive reinforcement helped reduce anxiety and encouraged task completion, while clear instructions and adaptive visual aids-maintained focus and continuity of learning. This study concluded that supportive, structured, and empathetic behavior management strategies play an important role in creating an inclusive English learning environment for students with ADHD.